2021
DOI: 10.3390/nu13093051
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Biological Metabolites as Food Intake Biomarkers, a Pending Signature for a Complete Understanding of the Beneficial Effects of the Mediterranean Diet

Abstract: The Mediterranean diet (MD) has become a dietary pattern of reference due to its preventive effects against chronic diseases, especially relevant in cardiovascular diseases (CVD). Establishing an objective tool to determine the degree of adherence to the MD is a pending task and deserves consideration. The central axis that distinguishes the MD from other dietary patterns is the choice and modality of food consumption. Identification of intake biomarkers of commonly consumed foods is a key strategy for estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…As mentioned previously, the MD is known for its benefits on health, which could explain why athletes, both professional and recreational, would strive towards this diet regime [40]. Our study shows that professional athletes had significantly higher adherence to this diet pattern than recreational athletes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As mentioned previously, the MD is known for its benefits on health, which could explain why athletes, both professional and recreational, would strive towards this diet regime [40]. Our study shows that professional athletes had significantly higher adherence to this diet pattern than recreational athletes.…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned previously, the MD is known for its benefits on health, which explain why athletes, both professional and recreational, would strive towards th regime [40]. Our study shows that professional athletes had significantly h Furthermore, multivariable logistic regression showed that the total MET min/week score (OR 1.0005, 95% CI 1.0003-1.0008, p < 0.001) and the MDSS score (OR 1.0836, 95% CI 1.0059-1.1672, p = 0.034) were significant predictors of high tendencies to ON behavior when computed along with baseline characteristics (Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…The metabolism of atmospheric oxygen produces highly reactive oxygen species (ROS) that can cause the oxidation of food constituents, including lipids, pigments, vitamins and proteins. The degradation process in food initiated by oxygen reactivity has the consequences of off-flavor formation, loss of color and the transformation of important nutrients, which decrease the quality of the food and are risk factors for the development of diseases [ 9 , 15 , 33 ]. Therefore, a dietary antioxidant can scavenge reactive oxygen/nitrogen species (ROS/RNS) to stop radical chain reactions, or it can inhibit the reactive oxidants from being formed in the first place (preventive).…”
Section: Potential Applications Of Phenolipidsmentioning
confidence: 99%
“…One of the main causes of health imbalance is related to oxidative stress, causing cell affectation because of their inability to stop damage by neutralizing free radicals, leading to numerous degenerative and chronic diseases [ 3 , 9 , 11 , 59 ]. The polyphenols present in the diversity of foods available in the human diet have demonstrated their capacity as antioxidant and protective agents against various degenerative diseases related to the imbalance between oxidative processes inherent to the cellular metabolism and mechanisms (endogenous and exogenous).…”
Section: Potential Applications Of Phenolipidsmentioning
confidence: 99%
See 1 more Smart Citation